2020
DOI: 10.1007/s00701-020-04484-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of machine learning models to prognosticate chronic shunt-dependent hydrocephalus after aneurysmal subarachnoid hemorrhage

Abstract: Background Shunt-dependent hydrocephalus significantly complicates subarachnoid hemorrhage (SAH), and reliable prognosis methods have been sought in recent years to reduce morbidity and costs associated with delayed treatment or neglected onset. Machine learning (ML) defines modern data analysis techniques allowing accurate subject-based risk stratifications. We aimed at developing and testing different ML models to predict shunt-dependent hydrocephalus after aneurysmal SAH. Methods We consulted electronic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…In neurosurgery, ML prediction models have been evaluated for a variety of pathologies with variable predictive performances (AUC 0.71 to 0.96) [26]. In the prediction of the occurrence of shunt-dependent hydrocephalus after aSAH, ML methods proved to be superior to traditional methods [24]. They included dynamic variables such as infections, treatment timing from symptom onset, and fever onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In neurosurgery, ML prediction models have been evaluated for a variety of pathologies with variable predictive performances (AUC 0.71 to 0.96) [26]. In the prediction of the occurrence of shunt-dependent hydrocephalus after aSAH, ML methods proved to be superior to traditional methods [24]. They included dynamic variables such as infections, treatment timing from symptom onset, and fever onset.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, we appliedamongst others-two of the most promising state-of-the-art ML techniques to predict functional outcome after aSAH: tree boosting and ANN. Both have shown considerable advances over traditional linear or logistic regression techniques in the past [12,38], even though traceability and comparability across different studies is reduced by substantial heterogeneity of clinical questions, input and output variables, and applied algorithms [19,24,26,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reviewed the literature to come up with a synopsis of the use of AI for outcome prediction in intracranial aneurysms (Table 4). In total, 24 studies were identified, and predicted outcomes encompassed occlusion rates after flow diversion, [26][27][28] perioperative outcomes after microsurgical treatment of unruptured aneurysms, 29 delayed cerebral ischemia, 9,[30][31][32][33][34][35] post-aSAH shunt-dependent hydrocephalus, 42,48 post-aSAH functional status at different time points (discharge until 1-year followup), 9,[35][36][37][38][39][40][41][42][43][44][46][47][48] and mortality 9,37,42,45 after aSAH. Most studies were published in the past 4 years (2018-2021), demonstrating that experience with this methodology is nascent and continuously evolving.…”
Section: Ai: External Validationmentioning
confidence: 99%
“…They concluded that building trust in these new technologies would require further improvement and more explanation of the ability and interpretability of applied models. Muscas and colleagues 9 analyzed different ML models to predict shunt-dependent hydrocephalus after aneurysmal subarachnoid hemorrhage. They suggested a single best distributed random forest model could be very helpful in identifying low-risk patients for shunt-dependency with an accuracy of 90%.…”
Section: Machine Learning-based Clinical Adjusted Selection Of Predicting Risk Factors For Shunt Infection In Childrenmentioning
confidence: 99%